CHARACTERIZATION OF FESE SUPERCONDUCTOR MATERIAL WITH MAGNESIUM DOPING VIA POWDER METALLURGY AND QUENCHING METHOD - Maulana, Muhammad Ilham (Jurnal Rekayasa Mesin, 2025)
The effect of magnesium (Mg) content on the resistivity, microstructure, and phase characteristics of iron selenide (FeSe) was investigated. The investigation employed the Powder in Sealed Tube (PIST) method to fabricate components with intricate geometries and high dimensional precision. MgₓFe₁₋ₓSe samples (x = 0; 0.01; 0.05; 0.1) were synthesized via hand milling of high-purity Fe, Se, and Mg powders, compacted in sealed Stainless Steel (SS) 316 tubes, and sintered at 845 °C for 6 h with water quenching. Resistivity was characterized based on electrical measurements at the low temperature, surface morphology was evaluated through Scanning Electron Microscope (SEM) imaging, and phase formation was identified via X-ray Diffraction (XRD) analysis. Based on normalized measurements, the addition of 5 at% Mg results in a resistivity reduction of up to ~39%, representing the most pronounced drop across the tested compositions. MgₓFe₁₋ₓSe samples exhibits a denser and more homogeneous appearance. FeSe samples doped with varying amounts of Mg display a bulky appearance, a hallmark feature associated with powder metallurgy techniques. The presence of β-FeSe phase identified through XRD testing validates the material's composition and crystalline structure, providing essential insights into its superconducting behavior and paving the way for further detailed characterization.